Efficiency Improvement of Permanent Magnet BLDC Motors for Electric Vehicles - Minh, D. B.; Quoc, V. D.; Huy, P. N. (Engineering, Technology & Applied Science Research, 2021)
A permanent magnet Brushless DC (BLDC) motor has been designed with different rotor configurations based on the arrangement of the permanent magnets. Rotor configurations strongly affect the torque and efficiency performance of permanent magnet electric motors. In this paper, different rotor configurations of the permanent magnet BLDC motor with parallel the Halbach array permanent magnet were compared and evaluated. Many applications of electric drives or air-crafts have recently preferred the surface-mounted permanent magnet design due to its ease of construction and maintenance. The finite element technique has been used for the analysis and comparison of different geometry parameters and rotor magnet configurations to improve efficiency and torque performance. A comprehensive design of a three-phase permanent magnet BLDC 35kW motor is presented and simulations were conducted to evaluate its design. The skewing rotor and Halbach magnet array are applied to the permanent surface-mounted magnet on the BLDC motor for eliminating torque ripples. In order to observe the skewing rotor effect, the rotor lamination layers were skewed with different angles and Halbach sinusoidal arrays. The determined skewing angle, the eliminated theoretically cogging torque, and the back electromotive force harmonics were also analyzed.